Analisis Implementasi Model Pembelajaran PBL (Problem Based Learning) Dalam Pembelajaran PKn Berbasis Media Interaktif SDN 1 Ambarawa - Auralia, Lufiana Sifa; Intani, Cenita Givia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted to examine the Implementation of the Problem Based Learning (PBL) Model in Civics Learning Based on Interactive Media. The case study approach used in the qualitative methodology collected data through in-depth interviews with students and teachers in the classroom. The results of the study revealed that the implementation of the Problem Based Learning (PBL) model in Civics learning using interactive media was carried out through regular steps, especially orientation to the problem, formulation and understanding of the problem, information collection and exploration, processing and analysis of information, preparation and presentation of solutions, reflection and evaluation of learning. It turned out that there were obstacles in its implementation, insufficient time, lack of learning resources, and differences in student abilities. This study provides a view of the implementation of the Problem Based Learning (PBL) model in Civics lessons that utilize interactive media and proposes solutions to improve the effectiveness of problem-focused learning by utilizing interactive media at the elementary school level.